Kesalahan Penggunaan Partikel Pada Klausa Relatif Mahasiswa Tingkat Dua di Kelas Menulis Artikel Populer Bahasa Jepang - Winingsih, Irma; Wahyuningsih, Tri Mulyani; Santoso, Budi (Vocational College of Diponegoro University, 2024)
This research examines errors in the use of particles in embedded clauses made by second semester students at the UDINUS Japanese Literature Study Program in the Writing Popular Japanese Articles class. The author considers that discussing this matter is very important considering that the ability to understand this embedded clause will be applied to the ability to speak, write, read and also translate. Apart from that, the ability to understand embedded clauses will support success in working on Reading questions on the Japanese JLPT test. The research method used is descriptive qualitative with a syntactic approach and interpretative techniques. The mistake students generally make is that it is still difficult to understand the use of the